Resilience Assessment of Road Networks in the Extremely Severe Disaster Areas of the Wenchuan Earthquake - Wei, Meng; Fang, Song Jing; Chen, Sang; Lin, Ran yi; Huang, Yong; Yang, Li (Frontiers in Earth Science, 2022)
On 12 May, 2008, a magnitude 7.9 earthquake struck Wenchuan County, Aba Tibetan and Qiang Autonomous Prefecture, Sichuan Province, causing substantial losses of human life and property. This paper takes ten counties and cities along the road network in the extremely severe disaster areas of the Wenchuan earthquake as research objects and extracts typical road network characteristics for 10 time points during the pre-earthquake, damage and repair processes. Then, it builds three resilience assessment indices, namely, the overall integrity, overall connectivity and effective connectivity with the complex network and resilience framework, to investigate the road network resilience. A resilience curve of the road system based on real data from the extremely severe disaster areas of the Wenchuan earthquake is obtained here for the first time, revealing the total variation characteristics and key sections of the road system in terms of resilience and proposing strategies for resilience optimization.